2018
DOI: 10.1002/pc.24942
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for predicting conductivity of polymer composites with a forced assembly network obtained bySCFNAmethod

Abstract: The Spatial Confining Forced Network Assembly, SCFNA, is a promising method for the preparation of high performance electrical conductive polymer composites, CPCs, by constructing a forced assembly conductive network in the polymer matrix. Because the present mathematical models for predicting electrical conductivities of CPCs were derived based on the free assembly of a conductive network, they were not suitable for predicting the electrical conductivities of the CPCs by SCFNA. A mathematical model for predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…In this case, it can be concluded that the application of an external force in the sample molding does not significantly affect the location and compactness of nanoscale fillers. Based on the theoretical foundation of SCFNA method, which is detailed in our earlier studies [35][36][37][38], it can be assumed that this method can be effective in case of producing samples with a limited thickness (~ 0.1-0.5 mm) comparable to the size of agglomerated clusters of filler particles (~ 400-600 μm). However, the possibility of manufacturing such thin samples for nanofillers is currently unavailable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, it can be concluded that the application of an external force in the sample molding does not significantly affect the location and compactness of nanoscale fillers. Based on the theoretical foundation of SCFNA method, which is detailed in our earlier studies [35][36][37][38], it can be assumed that this method can be effective in case of producing samples with a limited thickness (~ 0.1-0.5 mm) comparable to the size of agglomerated clusters of filler particles (~ 400-600 μm). However, the possibility of manufacturing such thin samples for nanofillers is currently unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…However, the high cost of the raw materials and the complexity of their processing still make it difficult to utilize these types of fillers in a high volume manufacturing process. In recent works [35][36][37][38], the SCFNA method was described on the example of thin films. The influence of this method on the electrical [36] and thermal [38] conductivity of thin composites based on PDMS matrix was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer materials are now widely used to fabricate the MNs because polymers are inexpensive and easy to mass production due to their uncomplicated fabrication and low cost. 1,3,[141][142][143] The most common manufacturing technique for polymeric MNs is micromolding method, including hot embossing, injection, and casting. [144][145][146][147][148] After the master mold for MNs are fabricated, MNs can be produced efficiently and stably via micromolding techniques until the mold breaks.…”
Section: Fabrication Of Polymeric Mnsmentioning
confidence: 99%
“…In this paper, PDMS was used as the substrate of the polymer-based flexible sensor, and the sensing elements and electrodes were assembled with carbon fiber as the conductive medium by a spatial confining forced network assembly method [14,15,16]. The sensing elements and the electrodes material, which were made of the same material, have the same telescopic matching property, which could improve the working range of deformation of the sensor and measured component under periodic load.…”
Section: Introductionmentioning
confidence: 99%